PEMBERDAYAAN CLEANING SERVICE FT-UNM MELALUI PEMANFAATAN LIMBAH SAMPAH ORGANIK MENJADI PUPUK KOMPOS - Sukainah, Andi; Marhayati, Marhayati; Putra, Reski Praja; Ramli, Hartini; Mukhlis, Andi Muhammad Akram (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The training activities carried out by the Makassar State University service team are a form of community empowerment program. The training carried out is an idea from the utilization of waste waste in the FT UNM environment. The purpose of this training is to empower cleaning service personnel at the Faculty of Engineering, Makassar State University (FT-UNM) by providing insight into skills in managing organic waste into compost. Furthermore, this training involved 20 FT cleaning service people. The training stages carried out by the service team include the stages of training and counseling, namely by providing training to cleaning services on ways to sort organic and inorganic waste and basic techniques for making compost fertilizer. Provision of a processing area, namely by providing a place for processing organic waste into compost, such as a special area in the FT-UNM environment which is equipped with the necessary equipment. Organic Waste Collection is taught how to identify and collect organic waste generated at FT-UNM, such as food waste, leaves, and other organic waste. The composting process is by teaching composting techniques which include mixing organic materials, aeration, and maintenance so that the composting process runs well. Utilization and marketing is after the compost is ready, it can be used for greening needs on campus or sold to the surrounding community as a product that has economic value.